2020
DOI: 10.3389/fgene.2020.00874
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on the Whole Exome Sequencing of Prostate Cancer in the Indian Phenotype Reveals Distinct Polymorphisms

Abstract: Prostate cancer (PCa) is the third most common cancer among men in India, and no next-generation sequencing (NGS) studies have been attempted earlier. Recent advances in NGS have heralded the discovery of biomarkers from Caucasian/European and Chinese ancestry, but not much is known about the Indian phenotype/variant of PCa. In a pilot study using the whole exome sequencing of benign/PCa patients, we identified characteristic mutations specific to the Indian sub-population. We observed a large number of mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Expression of COL6A1 is significantly elevated in different tumors such as lung, prostate, cervical and pancreatic cancer compared to normal tissues. Interestingly, our previous WES studies in PCa have identified COL6A1 as one of the causal genes [7], whereas, we also identified this through our RNA-seq analysis. COL6A1 was shown to be physically interacting with DNAJB11, APP along with some other genes.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Expression of COL6A1 is significantly elevated in different tumors such as lung, prostate, cervical and pancreatic cancer compared to normal tissues. Interestingly, our previous WES studies in PCa have identified COL6A1 as one of the causal genes [7], whereas, we also identified this through our RNA-seq analysis. COL6A1 was shown to be physically interacting with DNAJB11, APP along with some other genes.…”
Section: Discussionmentioning
confidence: 78%
“…Although studies have dealt with the genetics, genomics, and the environmental influence in causal of PCa, no association of genotype and phenotype employing the NGS approaches has been discussed in the Indian population. Recent studies from our lab using the whole-exome sequencing (WES) approach of PCa in India have yielded very promising results to identify causal genes specific to PCa with 30 causal genes to the Indian cohort and over 8 genes specific to Indian phenotype with variable degree of genetic disposition [7]. Whole transcriptome shotgun sequencing (WTSS) or RNA-sequencing (RNA-Seq) on the other hand is used to study regulation, developmental biology, clinical and health sector [8].…”
Section: Introductionmentioning
confidence: 99%
“…Only TNNI3, CTXN1, SLC27A5, HSPA12B , and ENSSSCG00000032730 presented increased RNA levels in P in at least three of the four samples ( Supplementary Table 4 ). According to the GTEx portal (dbGaP accession number phs000424.v8.ps ), TNNI3 , a component of the striated muscle filaments, is exclusively expressed in the heart although one study linked it to prostate cancer ( 30 ). CTXN1 is most highly expressed in the brain but it is also present at lower levels in several other tissues including testis, and its function is related to brain biology ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we performed a trio exome analysis with the use of two trio pipelines, viz . VarScan Trio and GATK joint calling pipelines on Congenital Pouch Colon (CPC) samples from our rare disease cohort (Mathur et al, 2018, Gupta et al 2021, Gupta et al 2022) and Prostate cancer (PCa) (Gupta et al 2020) which we have published earlier. We attempted to compare the benchmarking results by analysing four datasets with a high confidence variant call set by the Genome in a Bottle (GIAB) consortium besides considering a truth set for pipeline performance validation to confirm their association with disease-causing mutations in CPC and PCa.…”
Section: Introductionmentioning
confidence: 99%